2014
DOI: 10.1007/s11165-014-9440-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Taiwanese University Students’ Physics Learning Profiles and Their Role in Physics Learning Self-Efficacy

Abstract: The main purposes of this study were to identify Taiwanese university students' physics learning profiles in terms of their critical conceptions of learning physics and to compare their physics learning self-efficacy with the different learning profiles. A total of 250 Taiwanese undergraduates who were majoring in physics participated in this study and were invited to complete two instruments, physics learning profile and physics learning self-efficacy (PLSE). The main results indicated that, first, the two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 56 publications
4
24
0
1
Order By: Relevance
“…Overall, this study classified conceptions as reproductive, transitional, and constructive, which were consistent with the results in the study of T. J. Lin et al () that characterized the conceptions of learning physics into three levels based on a cluster analysis. Given that transitional conceptions of m‐learning play an intervening role between reproductive and constructivist conceptions, educators should promote students' m‐learning conceptions of focusing on continuous learning and achieving a higher status.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Overall, this study classified conceptions as reproductive, transitional, and constructive, which were consistent with the results in the study of T. J. Lin et al () that characterized the conceptions of learning physics into three levels based on a cluster analysis. Given that transitional conceptions of m‐learning play an intervening role between reproductive and constructivist conceptions, educators should promote students' m‐learning conceptions of focusing on continuous learning and achieving a higher status.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Lee et al () found that reproductive conceptions of learning science (i.e., testing, calculating, and practicing) were tied closely with learners' surface approaches to learning science, whereas constructivist conceptions (i.e., applying, understanding, and seeing in a new way) were highly pertinent to deep approaches. Many researchers drew a similar conclusion from the viewpoint of different subjects, such as physics (T. J. Lin et al, ), biology (Chiou et al, ), and computer science (Liang, Su, & Tsai, ).…”
Section: Literature Reviewmentioning
confidence: 85%
See 3 more Smart Citations